(untitled) (Global Journal of Science Frontier Research, 2014)
Ethanol tolerant saccharomyces species: Saccharomyces cerevisiae, Saccharomyces ovarum, Saccharomyce fragilis and Saccharomyce lactis were successfully isolated from 168 hours aged palmwine on glucose yeast extract agar at 28. The basic physiological parameters (pH and ethanol content) of the aged palmwine were investigated. Fermentative assessment test was carried out to determined and estimate the fermentative abilities of the four reference saccharomyces isolates on 15% glucose medium. The maximum ethanol content produced by the isolate varies between 8.1 to 10.8%v/v. Saccharomyces cerevisiae produced the highest while S. lactis had the lowest (8.1%).The fermentative ability of all the isolates was enormously affected after been subjected to mutagenic effects of subminimum inhibitory concentration (MIC) of acridine orange for 48hours to determined the genetic stability of each of the isolate. S. lactis was found to have lost all its fermentative property while both S. ovarum, and S. Fragilis lost its fermentative ability by 80% compared to S. cerevisiae that was stabilized to the mutagenic effects of acridine orange. Hence S. cerevisiae was confirmed to be the most genetically and mutagenically stabilized isolate compared to other isolates.